Learning tajweed via interactive mind map / Mohammad Ridhwan Talib - Talib, Mohammad Ridhwan (2014)
Interactive mind map has now become a need in study because it helps people to understand faster in the learning process. This research paper identifies an overview of interactive mind map. To identify the interactive mind map, the interface has been designed just like the real mind map on the paper but with the additional of some multimedia features such as video, graphics, and others. Basically, it is design to help people easily to understand the tajweed. The method that is being used to implement this application is Agile Development method. The reason why this method being chosen is because this method's concept is an iterative process which mean the stages may iterate from the beginning until it reach the delivery of the final product. Based on the result, the user seems to give a feedback which is this application is easy to use, easy to learn and easy to remember how to use. Therefore, this application can contribute to help students to learn about Tajweed in a fun and interactive way.